Pengaruh Digital Marketing, Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Merek PCX di Blora - Muhammad Adib Sugih Arto; Triyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Businesses need a strong marketing plan in order to boost the amount of product sales they create. Good use of functions for digital marketing, strong brand image and guaranteed quality products are needed for the right marketing strategy to promote company results. The population of customers in Blora Regency who buy motorcycles under the Honda PCX brand is considered in the study methodology. A questionnaire was utilized to collect data. Sample used 100 respondents. Multiple regression analysis is the analysis method employed. The results gained demonstrate that superior products, a well crafted brand image, and appropriate digital marketing elements significantly increase their influence on consumers' decisions to buy Honda PCX motorcycles in Blora Regency.